Pancasila And Citizenship Education E-Module Teaching Materials Using Google Classroom for Improving the Quality of Learning - Azzahra, Dinda; Arfan, Rocky; Moeis, Isnarmi; Indrawadi, Junaidi; Dharma, Surya (Universitas Pendidikan Ganesha, 2023)
The decline in the quality of learning has a destructive impact on the ability to think, the quality of education, and the quality of the human resources produced. The learning process, educators, and teaching materials are sources of inequality often encountered. This study aims to analyze the feasibility and capabilities of Civics teaching materials using Google Classroom to improve the quality of learning. This type of research is developed using the ADDIE model. Data was collected through direct observation, interviews, documentation and questionnaires. The data collection instrument used a questionnaire. The research subjects are teachers, media experts, and material experts. The test subjects were students. Data analysis was carried out descriptively in the form of percentages. The research results are that the E-module used as teaching material for Pancasila and Citizenship Education (PPKn) subjects can get a very good score of 90%. Material experts give these results a score of 88%, media experts score 82%, and teachers score 90% based on criteria that can be used in the field. It was concluded that e-modules designed and integrated with Google Classroom could interest students in the teaching and learning process.